Estimation of the permittivity and porosity of the lunar uppermost basalt layer based on observations of impact craters by SELENE. Issue 7 (23rd July 2013) - Ishiyama, Ken; Kumamoto, Atsushi; Ono, Takayuki; Yamaguchi, Yasushi; Haruyama, Junichi; Ohtake, Makiko; Katoh, Yuto; Terada, Naoki; Oshigami, Shoko
Abstract: [1] We have investigated the geological conditions below two lava flow units through determining the bulk permittivity and porosity in the uppermost basalt layer to depths of a few hundred meters. We use a newly developed method based on three data sets obtained by the Lunar Radar Sounder (LRS), Multiband Imager (MI), and Terrain Camera (TC) onboard the Selenological and Engineering Explorer (SELENE; Kaguya) spacecraft. The bulk permittivity of the uppermost basalt layer is calculated as the ratio of the apparent radar depth to the thickness of the uppermost basalt layer. Its thickness can be constrained from the excavation depths of two types of craters (haloed and nonhaloed craters). These craters are identified on the basis of FeO and/or TiO2 maps created from the MI data. These excavation depths are determined based on the measurement of the crater diameter using the TC data. The apparent radar depth is derived from the time delay between the surface echo and subsurface echo measured by LRS near the craters. The bulk permittivities are estimated to be 2.8–5.5 in a lava flow unit of Mare Humorum and 4.2–18.0 in a lava flow unit of Mare Serenitatis. These bulk permittivities are indicative of porous basalt layers with the porosities of 19%–51% in the unit of Humorum and 0%–33% in the unit of Serenitatis. The estimated porosities would be mainly explained by two different sources: intrinsic voids of lava and impact‐induced cracks. Key Points: The permittivitties of lunar basalt layers were estimated by a new method The permittivities estimated in the two mare regions were 2.8‐5.5 and 4.2‐18.0 Intrinsic voids and impact‐induced cracks were main porosity sources